THE ASPECTS OF UNIVERSAL DESIGN IN INTERIOR DESIGNING - Rangga Firmansyah; Tita Cardiah; Fajarsani Retno Palupi (Pendhapa, 2020)
Many studies show the findings of public facilities' cases still inaccessible to people with disabilities and see the importance of a design, especially in the interior sector, that can produce a built environment that is user-friendly and barrier-free. Accessibility rights for persons with disabilities have been regulated in various regulations ranging from regulations in the central government to laws, government regulations to the minister of public works and regional regulations. There is a regulation of the minister of public works and public housing of the Republic of Indonesia No.14 2017, which regulates the provision of facilities in buildings and environments according to the needs of all age groups and conditions of physical, mental, and intellectual limitations, or sensory-based on the function of the building to make it easier for users and visitors in their activities in public buildings. However, this guideline has not been discussed in detail. This research is intended to review universal design standards in the interior design process, especially in public buildings.